Pengabdian kepada Masyarakat melalui Digitalisasi dalam Meningkatkan UMKM di Desa Suka Makmur Kabupaten Langkat - Prames Wary Tri Wulandari; Misrah Misrah; Khairida Nur Rahmah; Satria Budi; Radiansyah Radiansyah (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity was conducted by the Community Service Program (KKN) team in Suka Makmur Village, Langkat Regency. The activity aimed to improve the digital literacy of Micro, Small, and Medium Enterprises (MSMEs) who are still limited in utilizing digital technology. This effort was carried out through training on "E-Commerce Development and MSME Registration on Google Maps." The methods used included field observation, interviews with MSMEs, and documentation of the activity. Data analysis was conducted descriptively to describe the implementation process, results, and impact on improving participants' digital skills. The results showed an increase in participants' understanding of registering their businesses on Google Maps, understanding the benefits of QRIS as a digital payment tool, and using social media for business promotion. Of the target 15 MSMEs, 6 successfully created active and verified Google Maps accounts. The main obstacles faced were limited internet access and digital devices. Overall, this activity contributed to expanding digital literacy and strengthening the competitiveness of MSMEs in Suka Makmur Village, while also supporting the achievement of Sustainable Development Goals (SDGs) 8 on decent work and sustainable economic growth.